2018
DOI: 10.1177/0003122418795856
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Intimate Partner Violence and the Risk of Pregnancy during the Transition to Adulthood

Abstract: Using a reproductive coercion framework, we investigate the role of intimate partner violence (IPV) in pregnancy during the transition to adulthood. We use two types of data from a population-based sample of 867 young women in a Michigan county: a 60-minute survey interview with 2.5 years of weekly follow-up surveys, and semi-structured interviews with a subsample of 40 pregnant women. The semi-structured interviews illustrate the violence women experienced. Discrete-time logit hazard models demonstrate that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 85 publications
1
20
0
Order By: Relevance
“…Pregnancy coercion is often described in the context of abusive, power-imbalanced relationships. 14,36,37 Consistent with the empirical literature, coercion was associated with physical and sexual abuse, as well as birth control sabotage. Whether in the context of an abusive relationship or not, male sex partners’ reproductive desires may take precedence over women’s reproductive choices, leading to unprotected sex and unwanted pregnancy.…”
Section: Discussionsupporting
confidence: 75%
“…Pregnancy coercion is often described in the context of abusive, power-imbalanced relationships. 14,36,37 Consistent with the empirical literature, coercion was associated with physical and sexual abuse, as well as birth control sabotage. Whether in the context of an abusive relationship or not, male sex partners’ reproductive desires may take precedence over women’s reproductive choices, leading to unprotected sex and unwanted pregnancy.…”
Section: Discussionsupporting
confidence: 75%
“…Rather, we speculate that nonmonogamous and physically violent relationships have other characteristics that are associated with pregnancy desire. For example, research has shown that violent young men are more likely than their nonviolent counterparts to want their girlfriends to get pregnant . In addition, Edin and Kefalas observed that young women with undesirably behaving partners hope that a pregnancy will cause them to settle down and start a family .…”
Section: Discussionmentioning
confidence: 99%
“…Microregulations of feminine performance (e.g., clothing) are key to coercive control (Anderson 2009). Abusers regulate women's bodies by controlling access to birth control and abortion (Barber et al 2018;Miller et al 2010). Research with male perpetrators further shows that abusive men hold traditional gender role ideologies (Anderson and Umberson 2001;Yamawaki, Ostenson, and Brown 2009) and tend to construct their female partners as unreasonable (Schrock, McCabe, and Vaccaro 2017).…”
Section: Gender Stereotypes and Intimate Relationshipsmentioning
confidence: 99%